A comparative analysis of an RC low-rise building with the seismic codes of countries lying in the Himalayas: China, India, Nepal, and Pakistan - Sanjaya Kunwar; Deepak Thapa; Achyut Paudel; Aayush Shrestha (Discover Civil Engineering)
Abstract The Himalayan region is one of the most seismically active areas in the world due to its tectonic setting. This vulnerability poses significant risks to buildings, resulting in substantial loss of life, property, and infrastructure. This study investigates the seismic performance of a reinforced concrete (RC) low-rise building using the seismic codes of countries situated along the Himalayan belt: China, India, Nepal, and Pakistan. These countries, despite sharing a common geological seismic threat, have developed a distinct code and standards for construction. This inconsistency concerns the effectiveness and suitability of seismic design practices in this region, hence prompting a comparative study. This study begins by reviewing the development of seismic codes in these countries. Subsequently, a prototype RC low-rise building was modeled and analyzed using finite element software, employing the linear static method of analysis according to each country's seismic codes. This study focused on key seismic responses, including the fundamental period, base shear, displacement, and story drift. The analysis revealed significant differences in seismic responses among the codes. Notably, the Chinese seismic code resulted in the highest values for the parameters studied, followed by the Nepalese, Pakistani, and Indian codes. The comparison revealed that the base shear from the Chinese code was the highest, being 3.10 times greater than the Indian code, 1.66 times greater than the Nepalese code, and 1.86 times greater than the Pakistani code. Similar ratios for displacements and story drifts were found in the study.